Asset Demand Based Tests of Expected Utility Maximization - Kubler, Felix; Selden, Larry; Wei, Xiao (American Economic Review, 2014)
We provide conditions under which contingent claim and asset demands are consistent with state independent Expected Utility maximization. The paper focuses on the case of a single commodity and demands are allowed to be functions of probabilities and not just prices and income. We extend prior analyses by deriving three distinct tests for demands to be rationalized by Expected Utility: (i) a contingent claim analogue to the certainty strong axiom of revealed preference, (ii) a characterization of the functional form for demand, and (iii) necessary and sufficient conditions based on the Slutsky matrix. (JEL D01, D11, D81)